Azithromycin for treatment of bronchiolitis obliterans syndrome in adult lung transplant recipients - Safavi, Shahideh; Prayle, Andrew P.; Hall, Ian P.; Parmar, Jasvir (Wiley, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: This review aims to look at the benefits and harms of azithromycin for the treatment of BOS in adult lung transplant recipients.